2021
DOI: 10.1021/acsami.0c21134
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Polymer-Assisted Metal Oxide Hybrid Semiconductors for High-Performance Thin-Film Transistors

Abstract: Metal oxide semiconductors doped with additional inorganic cations have insufficient electron mobility for nextgeneration electronic devices so strategies to realize the semiconductors exhibiting stability and high performance are required. To overcome the limitations of conventional inorganic cation doping to improve the electrical characteristics and stability of metal oxide semiconductors, we propose solution-processed high-performance metal oxide thin-film transistors (TFTs) by incorporating polyaniline (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…), [20][21][22][23] by organic bulk doping to intentionally frustrate the crystallization. [24][25][26] Nevertheless, most of the previous reports on solution-processed MO films utilize toxic solvents, which result as a potential threat to the environment. Liu et al reported the MO-TFTs by using an aqueous precursor solution and studied the annealing time and low temperature effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), [20][21][22][23] by organic bulk doping to intentionally frustrate the crystallization. [24][25][26] Nevertheless, most of the previous reports on solution-processed MO films utilize toxic solvents, which result as a potential threat to the environment. Liu et al reported the MO-TFTs by using an aqueous precursor solution and studied the annealing time and low temperature effect.…”
Section: Introductionmentioning
confidence: 99%
“…), [ 20–23 ] by organic bulk doping to intentionally frustrate the crystallization. [ 24–26 ] Nevertheless, most of the previous reports on solution‐processed MO films utilize toxic solvents, which result as a potential threat to the environment. Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…25 Boratto et al reported that the lowest unoccupied molecular orbital (LUMO) of the organic molecules can also act as trap states for electrons from the MO CBM. 26 In particular, by adding polyaniline (PANI) into the InO x precursor, Kim and coworkers 27 enhanced the overall electrical characteristic of MOTFTs, proving that conductive polymers could decrease the trap density in the InO x semiconductor by orbital overlapping.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, TIPS-pentacene increases the percolation for electrons, providing an electron pathway where the InO x films have structural defects or have voids. 27 In the hybrid films, TIPS-pentacene was deposited with controlled thicknesses by physical vapor deposition. We find that the addition of vacuum-deposited TIPS-pentacene to singly coated InO x films creates devices with mobilities that are otherwise only measured after three InO x coating steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation